2018
DOI: 10.1063/1.5025036
|View full text |Cite
|
Sign up to set email alerts
|

PIEZO channel protein naturally expressed in human breast cancer cell MDA-MB-231 as probed by atomic force microscopy

Abstract: Mechanical stimuli drives many physiological processes through mechanically activated channels, and the recent discovery of PIEZO channel has generated great interests in its mechanotransduction. Many previous researches investigated PIEZO proteins by transcribing them in cells that originally have no response to mechanical stimulation, or by forming PIEZO-combined complexes in vitro, and few studied PIEZO protein’s natural characteristics in cells. In this study we show that MDA-MB-231, a malignant cell in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Piezo is highly conserved and has already been linked to a large number of mechanically sensitive processes (23,24,29,30,(61)(62)(63)(64). Following this Dictyostelium precedent, we see no reason why many other types of migrating cell should not also sense their mechanical environment through Piezo.…”
Section: Discussionmentioning
confidence: 94%
“…Piezo is highly conserved and has already been linked to a large number of mechanically sensitive processes (23,24,29,30,(61)(62)(63)(64). Following this Dictyostelium precedent, we see no reason why many other types of migrating cell should not also sense their mechanical environment through Piezo.…”
Section: Discussionmentioning
confidence: 94%
“…In the latter case, the role of Piezo channels is even substantiated by the fact that the survival time of the breast cancer patients is negatively related to the mRNA expression level of Piezo1 in the primary tumor [ 18 ]. Interestingly, it has been shown that the response of breast cancer cells to compression is dependent on Piezo but not TRP channels [ 19 ]. And upon activation of Piezo channels (Piezo1 in particular), the corresponding calcium influx evokes several downstream signaling pathways including Src and extracellular regulated protein kinase (ERK) which in turn affect the dynamics of actin-based protrusion structures such as invadopodia/invadosomes that degrade ECM proteins and thus promote invasion [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…One candidate is the piezo channel reported in both MDCK ( 58 ) and HEK293T cells ( 59 ). However, piezo channels are not sensitive to SKF96365 ( 60 ), which inhibited transient induction ( Fig. 4 , C and D ).…”
Section: Discussionmentioning
confidence: 95%